2017
DOI: 10.12659/msm.907730
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Quality of Life: Exploring the Mediator Role of Social Support in Patients with Breast Cancer

Abstract: BackgroundThe diagnosis and treatment of breast cancer can provoke a series of negative emotional changes in patients, further affecting their quality of life. It has been shown that patients with higher resilience have better quality of life. Social support systems are important protective factors that are necessary for the process of resilience to occur. Hence, this study aimed to investigate the role of social support in the relationship between resilience and quality of life among Chinese patients with bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
169
1
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(204 citation statements)
references
References 53 publications
21
169
1
13
Order By: Relevance
“…The results also showed that the number of non-recurrence patients at the high social support level (means higher than 4) (88.6%) and women with recurrence at the low level of social support (less than 3) (71.4%) was high. The results of the study by Orsini and colleagues in France (2016) [21], by Jalali-Farahani et al in Iran (2018) [22], by Denewer and colleagues in Egypt (2016) [17], by Yang et al in China (2017) [23], by Suwankhong and Liamputtong in Thailand (2016) [24], by Zhang and colleagues in China (2017) [25], by Gage-Bouchard in the United States (2017) [26], by Thompson and colleagues in the United States (2017) [27], by Faller et al (2016) in Germany [28], by Kauffmann et al in the United States (2016) [29], and by Hulbert-Williams et al study (2018) [30]showed that social support and its dimensions had positive effects on patients' health, hope, quality of life, coping behavior, and body image, that are consistent with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The results also showed that the number of non-recurrence patients at the high social support level (means higher than 4) (88.6%) and women with recurrence at the low level of social support (less than 3) (71.4%) was high. The results of the study by Orsini and colleagues in France (2016) [21], by Jalali-Farahani et al in Iran (2018) [22], by Denewer and colleagues in Egypt (2016) [17], by Yang et al in China (2017) [23], by Suwankhong and Liamputtong in Thailand (2016) [24], by Zhang and colleagues in China (2017) [25], by Gage-Bouchard in the United States (2017) [26], by Thompson and colleagues in the United States (2017) [27], by Faller et al (2016) in Germany [28], by Kauffmann et al in the United States (2016) [29], and by Hulbert-Williams et al study (2018) [30]showed that social support and its dimensions had positive effects on patients' health, hope, quality of life, coping behavior, and body image, that are consistent with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…24 Some studies have shown that there is a positive correlation between the level of psychological resilience of patients and the quality of life. 25 For example, patients with high level of psychological resilience have relatively good quality of life in all aspects, 26 and improving the resilience can promote the quality of life of ovarian cancer patients. 27 Resilience also has been reported to mitigate the negative psychological factors and contribute to increase the quality of life of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing interest in determining the psychosocial factors that may enhance HRQoL in BC patients [4][5][6][7], and the positive impact of a supportive social network has been reported [8].…”
Section: Introductionmentioning
confidence: 99%